BUDAYA MANAJEMEN SYARIAH, SISTEM REWARD DAN KINERJA KARYAWAN - Animah, Animah; Herwanti, Titiek (Jurnal Ilmiah Akuntansi Indonesia, 2019)
Abstract:This research was conducted to determine the effect of Sharia management culture which consists of prioritizing morals, prioritizing learning, prioritizing service, prioritizing the partnership and internalization of religion in the life of a leader and rewarding the performance of Baitul Maal Wat Tamwil (BMT) employees in Lombok. This research was conducted by distributing questionnaires. The population in this study were employees of the credit department. The sampling technique used in this study was purposive sampling with consideration of questionnaires that were returned and completely filled out by respondents. The total collected and complete to be processed in this study is 144 questionnaires. Analysis of the data used is SPSS version 23 by using multiple linear regression analysis techniques. The results showed that the culture of Sharia management and reward systems had a positive effect on employee performance.Keywords: Sharia Management Culture, Reward System, Employee Performance